Evaluation of renal function of sickle cell children in Libreville by estimation of glomerular creatinine-cystatin C filtration rate: prevalence of acute kidney injury and associated factors - Mintoo, Steeve; Loembe, Fifi C.; Mpira, Sylvie; Nguemou, Nathalie; Siawaya, Joel Djoba; Koko, Jean; Ategbo, Simon J. (International Journal of Contemporary Pediatrics, 2024)
Background: Sickle cell disease (SCD) is an important and growing global health problem. Kidney damage is one of the most common complications of SCD. We aimed to determine the prevalence of acute kidney injury (AKI) in children with SCD in our context. Methods: Cross-sectional and analytical study from January 2022 to September 2022, including SCD children aged from 6 months to 17 years during their hospitalisation. We measured the estimated glomerular filtration (eGFR) rate using the combined creatinine and cystatin C formula for kids (CKiDScr-Cys C). Univariate analyses were performed to measure the relationship between variables and AKI and eGFR, followed by a multivariate analysis using logistic regression. Results: Of the 137 children, we included 82 boys (60%) and 55 girls (40%). The mean eGFR was 112±45.3 ml/min/1.73 m2. A total of 36 subjects, or 26.3% (95% CI [18.9-33.6%)), had acute AKI. Comparison of characteristics by AKI status showed significant differences according the number of transfusions (p<0.01), and hemoglobin level (p<0.027), eGFR had a negative correlation with the number of transfusions r=-0.308 (-0.477; -0.117); p<0.01. Multivariate analysis showed that nutritional status was a protective factor of AKI (p<0.01), and the number of transfusions was a predictive factor of AKI in SCD in our context (p<0.001). Conclusions: The results from our study are an urgent alarm to implement the existing management programs on SCD from screening to universal access of hydroxyurea in order to reduce complications and mortality related to this pathology.